Factors influencing parents’ decision in choosing private schools - Yaacob, Noor Alyani; Mohamed Osman, Mariana; Bachok, Syahriah (Elsevier, 2014)
This research examines the factors considered by parents when deciding to enroll their children in private schools. Based on literature review, some eight factors have been identified, but this research only deals with four. According to the data analysis, parents part emphasizing on the importance of private schools’ syllabus, schools’ environment and facilities when selecting to enroll their children in private schools. The academic performance of the school was placed third in preference, with fourth factor considered being the quality teachers that the school possessed. The research was conducted by using quantitative approaches and carried out via structural self–administrated closedended questionnaires through questionnaire survey method.